2016
DOI: 10.1111/ppe.12296
|View full text |Cite
|
Sign up to set email alerts
|

Birth Outcomes in a Prospective Pregnancy–Birth Cohort Study of Environmental Risk Factors in Kuwait: The TRACER Study

Abstract: Background Rapid development and westernisation in Kuwait and other Gulf states have been accompanied by rising rates of obesity, diabetes, asthma, and other chronic conditions. Prenatal experiences and exposures may be important targets for intervention. We undertook a prospective pregnancy–birth cohort study in Kuwait, the TRansgenerational Assessment of Children’s Environmental Risk (TRACER) Study, to examine prenatal risk factors for early childhood obesity. This article describes the methodology and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
(37 reference statements)
3
8
1
Order By: Relevance
“…Similarly the rates of LBW (5.5%) were below the global estimate of 16% in 2013 [66] and the regional average for the EMR (19.3%) [67]. The observed rate of SGA (6.7%) is in agreement with that reported recently from a birth cohort in Kuwait (7.4%) [68], while the rate of macrosomia (4.3%) was within the range described for both developing (0.5–14.9%) and developed countries (5–20%) [6870]. As for LGA, its prevalence (24.6%) was similar to that reported from a recent study in Kuwait [68], while being higher than estimates reported from Italy and China (5.3–10.6%) [71, 72].…”
Section: Discussionsupporting
confidence: 83%
“…Similarly the rates of LBW (5.5%) were below the global estimate of 16% in 2013 [66] and the regional average for the EMR (19.3%) [67]. The observed rate of SGA (6.7%) is in agreement with that reported recently from a birth cohort in Kuwait (7.4%) [68], while the rate of macrosomia (4.3%) was within the range described for both developing (0.5–14.9%) and developed countries (5–20%) [6870]. As for LGA, its prevalence (24.6%) was similar to that reported from a recent study in Kuwait [68], while being higher than estimates reported from Italy and China (5.3–10.6%) [71, 72].…”
Section: Discussionsupporting
confidence: 83%
“…The stillbirth rate (SBR) of 46.2 per 100 births (95% CI:32.7-59.3) found in our study is higher than the data reported by hospital -based study in 2005 [5] and the data collected from a sub-national household survey conducted in six rural districts of four Yemeni provinces in 2008-2009 [17]. It is also higher than SBR in other EMR countries such as Kuwait [18], Palestine [19] and Pakistan [20]. Our study was a community-based study within households in Yemen, and the burden of stillbirths can be expected to be much higher at home than the hospital setting.…”
Section: Discussioncontrasting
confidence: 81%
“…Summary of the reviewed 81 published cohort studies according to the measured six exposure and two outcome domainsSociodemographic exposuresMaternal age was a common measured sociodemographic exposure studied in 18 cohort studies. Advanced maternal age was associated with GDM, CS, and preterm delivery[51,53,58,92,111,113]. Primary education or less was independently associated with 69% lower likelihood of exclusive breastfeeding at 6 months (aOR, 0.31; 95% CI, 0.11-0.88)[58] (see Additional file 3:Table S2).…”
mentioning
confidence: 99%
“…,43-50, 56, 57, 62-72, 79, 80, 82-98, 105-112], followed by eight (9.9%) in Kuwait[20,21,24,41,51,73,81,99], seven (8.6%) in each of Qatar[42,52,53,60,61,74,113] and the UAE[58, 59, 75-77, 100, 101], six (7.4%) in Oman…”
mentioning
confidence: 99%